EDIT LIKE A PRO WITH iMOVIE leverage Apple's free editor for iOS, iPadOS, and macOS and enrich videos with Keynote animations (PACKT PUBLISHING LIMITED, 2023)
A comprehensive guide to making the most of Apple's entry-level editing software--from the basics of editing to using iLife and open source apps to create unique non-fiction videos Key Features Learn editing principles as you assemble coherent and concise videos Master basic editing tools by importing, assembling, reframing, and embellishing footage with overlays and effects Customize animations and exports in iMovie and learn how to avoid the gotchas Apple won't tell you about Book Description It's not about having the shiniest tools; it's what you do with them. iMovie offers Apple users the ease of creating engaging videos using the free video editing application's support for macOS, iOS, and iPadOS devices. Complete with step-by-step tutorials for essential tools and concepts and explanations for why you should use them, this practical guide to iMovie will leave you well-prepared for the world of post-production. This book begins with an introduction to some of the core principles of editing. You'll learn how to easily make your videos coherent and concise and flex your creative muscles with Magic Movie and the Storyboard mode. Once you grasp how to use iMovie's full-blown Movie modes for mobile devices and macOS, you'll be able to use simple editing tools to deliver effective videos from import to export. Finally, you'll explore Keynote for creating custom titles and animations and building a personal visual brand that makes your videos uniquely yours. By the end of this iMovie book, you'll be on your way to becoming a creative problem-solver, using iMovie and other free apps to create high-quality, engaging videos for projects with different visual and technical requirements. What you will learn Soak up the principles of editing--coherence, conciseness, and adding meaning Use iMovie's Magic Movie and Storyboard tools to create simple, themed videos Navigate movie mode for iOS, iPadOS, and macOS and create videos without a template Improve the viewing experience with overlays and use keyframes for smooth animations Create custom titles and animations using Keynote Use open source software to transcode your exports for different platforms and requirements Identify the most common problems with iMovie and how to avoid them Who this book is for If you have an Apple device and have to make a video for work or school, this book is where to turn. Suitable even for absolute beginners, this book includes simple, progressive guides to help you master editing principles and employ iMovie to create simple but effective videos to inform, educate and entertain your colleagues, friends, and family. For more advanced users such as YouTubers and other online content creators, this book contains valuable tips on how to stamp unique identity and brand USPs into videos.